2010
DOI: 10.1089/vbz.2009.0154
|View full text |Cite
|
Sign up to set email alerts
|

Seewis Virus: Phylogeography of a Shrew-Borne Hantavirus in Siberia, Russia

Abstract: This is the first definitive report of shrew-borne hantaviruses in Siberia, and demonstrates the impressive distribution of SWSV among phylogenetically related Sorex species. Coevolution and local adaptation of SWSV genetic variants in specific chromosomal races of S. araneus may account for their geographic distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 39 publications
(37 reference statements)
6
35
0
3
Order By: Relevance
“…In this regard, phylogenetic segregation of TPMV sequences according to the geographic origin of the reservoir host species resembled that shown recently for Seewis virus in Sorex araneus 24,25 and MJNV in Crocidura lasiura . 16 These data were also consistent with the geographic-specific lineages shown previously for rodent-borne hantaviruses, including HTNV in Apodemus agrarius , 26 Soochong virus in Apodemus peninsulae , 27 Puumala virus in Myodes glareolus , 28,29 Muju virus in Myodes regulus , 30 and Tula virus in Microtus arvalis .…”
supporting
confidence: 77%
“…In this regard, phylogenetic segregation of TPMV sequences according to the geographic origin of the reservoir host species resembled that shown recently for Seewis virus in Sorex araneus 24,25 and MJNV in Crocidura lasiura . 16 These data were also consistent with the geographic-specific lineages shown previously for rodent-borne hantaviruses, including HTNV in Apodemus agrarius , 26 Soochong virus in Apodemus peninsulae , 27 Puumala virus in Myodes glareolus , 28,29 Muju virus in Myodes regulus , 30 and Tula virus in Microtus arvalis .…”
supporting
confidence: 77%
“…Seewis virus (SWSV), originally detected in the Eurasian common shrew (Sorex araneus) in Switzerland (Song et al 2007), has now been found across the vast distribution of its soricine reservoir host in the Czech Republic (Schlegel et al 2012), Finland (Kang et al 2009a, Ling et al 2014, Germany (Schlegel et al 2012), Hungary (Kang et al 2009a), Poland , Russia (Yashina et al 2010), Slovakia (Schlegel et al 2012), and Slovenia Resman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Однако интерпретация выявленных различий затруднена, поскольку в выборке есте-ственных хозяев хантавирусов -мышевидных грызунов -было всего 8 особей. Тем не менее, эти результаты свидетельствуют о том, что хантавирусы продолжают циркулировать среди мелких млекопи-тающих на территории Прибайкалья, где нами ранее подтверждено существование природных очагов [6,9,12]. Обнаружение антигена возбудителей ГЛПС в тканях байкальской нерпы может свидетельствовать о тесных контактах байкальских эндемиков с остров-ными или прибрежными млекопитающими и/или циркуляции в экосистеме оз.…”
Section: результаты и обсуждениеunclassified
“…В европейской части РФ тяжёлые фор-мы ГЛПС ассоциированы с вирусом Dobrava/Belgrad (DOBV) генотипа Sochi (носитель -кавказская лесная мышь), а для вирусов DOBV генотипа Kurkino (носи-тель -полевая мышь, европейский подтип) и Puumala (носитель -рыжая полёвка) характерно более лёгкое течение болезни [1,4,14]. Остальные хантавирусы, обнаруженные в РФ, либо не патогенны, либо их па-тогенность для человека не изучена [1,7,8,9,11,12].…”
unclassified
See 1 more Smart Citation